I Like Dangdut Chalange Dangdut sebagai Sebuah Society of Spectacle - Fitri, Alifa Nur (Interaksi: Jurnal Ilmu Komunikasi, 2016)
Abstraksi:Now, we find so many challenge for charity, one of them and popular is Ice Bucket Challenge. The goal of challenge to helpsÂ  researchÂ  ALS disease, and this challenge success to help them. One of program television in Indonesia, Indosiar make a same challenge. This challenge not for help ALS patient but for help many children to get educate more better, and this program name is â€œI Like Dangdut Challengeâ€. I Like Dangdut Challenge is one of program in â€œDâ€™Terong Showâ€one of popular dangdutÂ  program in Indosiar. This is form of epigonism, ALS get good response from people and Indosiar create same challenge to get good response too. Why Dangdut,not another genre music? Because Dangdut is music from Indonesia and many people young or old can enjoy it. This challenge invite artist, actor, public officials, minister, district head and society to show and dancing with dangdut music, and upload they video in Indosiar. Some public figure was following â€œI Like Dangdut Chellengeâ€ is Aliando and Prily Ratuconsina, Ganjar Pranowo GovernoorÂ  of Central Java, Ridwan Kamil Distric Head of Bandung, CEO of Semen Indonesia Dwi Soetjipto, Ignasius Jonan, Emirsyah Satar and Dahlan Iskan. Â Â  Andrew N. Weintraub describtion Dangdut asÂ  repertoire (of song, text, and spin off stylke), a community(singer, arranger, mucisians, produser, and fans) a performance style (spectacular, excessive, and over the top) and a discource abaout social relations of power.Â Â Â  (Andrew, 2010:15). And now Dangdut is different, not only for underclass but highclass too. Media make dangdut as a spectacle for society, from reality and make it to be a spectacle. Dangdut is a commodity for owner media, to get money, and the ways to society approve it is make it a spectacle to society. Keywords: Spectacle, Epigonism, Economy Political Media.